The urgent need for contemporary clinical trials in patients with asymptomatic carotid stenosis. (22nd November 2016) - Chaturvedi, Seemant; Chimowitz, Marc; Brown, Robert D.; Lal, Brajesh K.; Meschia, James F.
Abstract : Asymptomatic extracranial internal carotid artery atherosclerotic stenosis increases with age and is more common in men. Studies performed more than 2 decades ago showed that carotid endarterectomy reduced the rate of stroke in carefully selected patients with asymptomatic carotid stenosis compared with medical therapy in the long term. Those trials were completed more than 20 years ago and with advances in the treatment of atherosclerotic disease, the question has been raised to as to whether endarterectomy is still of value for patients with asymptomatic narrowing. Perioperative risk of carotid revascularization procedures has also declined. Due to improvements in both medical and surgical treatments for carotid artery stenosis, it is timely to reevaluate the efficacy of carotid intervention relative to medical treatment for patients with asymptomatic stenosis.